Perancangan model integrasi manajemen operasi pelayanan tanker menggunakan metode soft system methodology - Fuad Fatahillah; Saryanto Saryanto; Sawarni Hasibuan (Universitas Mercu Buana, 2019)
These study aims are to design a management model of integrated tanker shipping operations to create the best coordination of the parties involved in tanker shipping operations. The implementation of this model is expected to improve efficiency, effectiveness, and optimization of tanker shipping operations management in decision making appropriate and timely. The method used is the Soft System Methodology (SSM). Data was collected through Focus Group Discussion (FGD), In-Depth Interview (IDI) from experts. Human Activity System (HAS) mapping is done with analysis techniques using CATWOE analysis (Customer, Actor, Transformation, World view, Owner, Environment constraint), the model is designed through the SSM Learning Model which aims to design a Conceptual Model (CM). The management concept model of integrated tanker shipping operations has the implication of minimizing and eliminating cost losses due to claims so that it can reduce the cost of transporting fuel oil significantly so as to provide added value to the Government in carrying out the obligation to supply fuel at affordable economic prices throughout the Indonesian Unitary Territory.